Globalisation and union opposition to technological change - Straume, Odd Rune (2006)
Trade unions have a rational incentive to oppose the adoption of labour-saving technology when labour demand is inelastic and unions care much for employment relative to wages. Trade liberalisation typically increases trade union technology opposition. These conclusions are reached in a model of unionised international duopoly with two-way trade. We also find that the incentive for technology opposition is stronger in the more technologically advanced country and in the country with the larger home market, complementing earlier explanations for technological catch-up and leapfrogging.